ChemInform Abstract: Energy Transfer from Bi3+ to Ho3+ Triggers Brilliant Single Green Light Emission in LaNbTiO6:Ho3+, Bi3+ Phosphors. Issue 32 (24th July 2014) - Zhang, Xingshuang; Zhou, Guangjun; Zhou, Juan; Zhou, Haifeng; Kong, Peng; Yu, Zhichao; Zhan, Jie
Abstract: Pure and Ho 3+, Bi 3+ co‐doped LaNbTiO6 phosphors are synthesized by a sol—gel and combustion method using La2 O3, Ho2 O3, Bi(NO3 )3, Nb2 O5, Ti(O‐Bu)4, HNO3, HF, NH4 NO3, and citric acid as starting materials.